PENGARUH INOVASI KURIKULUM TERHADAP MINAT CALON MAHASANTRI MA’HAD ALY DARUSSALAM BLOKAGUNG - Siti Aimah; Mila Agustina (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The purpose of this study was to determine: (1) Curriculum innovation ma'had aly Darussalam Blokagung. (2) Interest of prospective students of Ma'had Aly Darussalam Blokagung. (3) The effect of knowing the effect of curriculum innovation on the interest of prospective students of Ma'had Aly Darussalam Blokagung. This study uses a quantitative descriptive method. The results of this study indicate that: (1) Curriculum innovation of Ma'had Aly Darussalam Blokagung Tegalsari Banyuwangi is classified as good, because the T-test results are 7.885 > 1.29025 t table, which means Ha is accepted; (2) The interest of prospective students of Ma'had Aly Blokagung is good, because the results of the T-test are 6.832 > 1.29025 t table, which means Ha is accepted; (3) there is the effect of curriculum innovation on the interest of prospective students of Ma'had Aly Darussalam Blokagung Tegalsari Banyuwangi by 46.0% while the remaining 54.0% is influenced by other variables not examined, which means that there is an influence of curriculum innovation on the interests of prospective students of Ma' had Aly Darussalam Blokagung Tegalsari Banyuwangi.